Racial differences in tuberculosis infection in United States communities: the coronary artery risk development in young adults study - Nahid, Payam; Horne, David J; Jarlsberg, Leah G; Reiner, Alexander P; Osmond, Dennis; Hopewell, Philip C; Bibbins-Domingo, Kirsten (Clinical infectious diseases, 2011)
Previously reported associations between race/ethnicity and tuberculosis infection have lacked sufficient adjustment for socioeconomic factors. We analyzed race/ethnicity and self-reported tuberculosis infection data from the Coronary Artery Risk Development in Young Adults (CARDIA) study, a well-characterized cohort of 5115 black and white participants, and found that after adjusting for sociodemographic and clinical factors, black participants were more likely to report tuberculosis infection and/or disease (odds ratio, 2.0; 95% confidence interval, 1.5-2.9).